2016
DOI: 10.1017/s0021859616000897
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to climate change for food security in the Rift Valley dry lands of Ethiopia: supplemental irrigation, plant density and sowing date

Abstract: SUMMARYStudies on climate impacts and related adaptation strategies are becoming increasingly important to counteract the negative impacts of climate change. In Ethiopia, climate change is likely to affect crop yields negatively and therefore food security. However, quantitative evidence is lacking about the ability of farm-level adaptation options to offset the negative impacts of climate change and to improve food security. The MarkSim Global Climate Model weather generator was used to generate projected dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 76 publications
4
41
0
2
Order By: Relevance
“…Our analysis indicated that late planting in Bako and Melkassa, and mid-window planting in Hawassa, combination with recommend fertilization application provided highest yield in all stations. In line with our results, Muluneh et al (2017), Kassie et al (2015) and Biazin and Sterk (2013) in Ethiopia, reported an increase in maize yields with delayed planting dates and nitrogen application for climate change scenarios. The significant impact of late planting would concur with works from Biazin and Sterk (2013) suggesting to wait for sufficient moisture needed for an efficient seed germination.…”
Section: Melkassa a Semi-arid Areasupporting
confidence: 91%
“…Our analysis indicated that late planting in Bako and Melkassa, and mid-window planting in Hawassa, combination with recommend fertilization application provided highest yield in all stations. In line with our results, Muluneh et al (2017), Kassie et al (2015) and Biazin and Sterk (2013) in Ethiopia, reported an increase in maize yields with delayed planting dates and nitrogen application for climate change scenarios. The significant impact of late planting would concur with works from Biazin and Sterk (2013) suggesting to wait for sufficient moisture needed for an efficient seed germination.…”
Section: Melkassa a Semi-arid Areasupporting
confidence: 91%
“…In Ethiopia, land degradation is the most severe problem that affects agricultural productivity and negatively affects food security [31,35,120,121]. According to the World Bank statistical estimate, land degradation cost to annual agricultural GDP ranges from 2% to 6.75% [122].…”
Section: Discussionmentioning
confidence: 99%
“…Agriculture sector, which accounts for about 50% of the Gross Domestic Product (GDP), 85% of the total export revenue, and over 80% of the total employment, is the main source of the country's economy [21][22][23][24][25]. The great majority of the population is dependent on subsistence agriculture that is an overwhelming vulnerable to the recurrent droughts and land degradation [21][22][23][24][25][26][27][28]. Rapid population increase and growing demand posed a greater pressure on land resources, leading to severe soil erosion and land degradation in various parts of the country.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that the land degradation cost to an annual agricultural GDP range from 2% to 6.75% [21]. The loss of topsoil by water erosion in Ethiopia was estimated at 1.5 billion tons per annum with a mean erosion rate of 42 t ha −1 y −1 [27,28]. However, the magnitude of soil erosion rates varies across the physiographical regions in the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation